Reactivation of cytomegalovirus and bloodstream infection and its impact on early survival after allogeneic haematopoietic stem cell transplantation: a multicentre retrospective study - Ren, Jinhua; Xu, Jingjing; Sun, Jiaqi; Wu, Xueqiong; Yang, Xiaozhu; Nie, Chengjun; Lan, Lingqiong; Zeng, Yanling; Zheng, Xiaoyun; Li, Jing; Lin, Qiaoxian; Hu, Jianda; et al. (Frontiers in Microbiology, 2024)
Cytomegalovirus reactivation (CMVr) and bloodstream infections (BSI) are the most common infectious complications in patients after allogeneic haematopoietic stem cell transplantation (allo-HSCT). Both are associated with great high morbidity while the BSI is the leading cause of mortality. This retrospective study evaluated the incidence of CMVr and BSI, identified associated risk factors, assessed their impact on survival in allo-HSCT recipients during the first 100 days after transplantation. The study comprised 500 allo-HSCT recipients who were CMV DNA-negative and CMV IgG-positive before allo-HSCT. Among them, 400 developed CMVr and 75 experienced BSI within 100 days after allo-HSCT. Multivariate regression revealed that graft failure and acute graft-versus-host disease were significant risk factors for poor prognosis, whereas CMVr or BSI alone were not. Among all 500 patients, 56 (14%) developed both CMVr and BSI in the 100 days after HSCT, showing significantly reduced 6-month overall survival (p=0.003) and long-term survival (p=0.002). Specifically, in the initial post-transplant phase (within 60 days), BSI significantly elevate mortality risk, However, patients who survive BSI during this critical period subsequently experience a lower mortality risk. Nevertheless, the presence of CMVr in patients with BSI considerably diminishes their long-term survival prospects. This study provides real-world data on the impact of CMVr and BSI following transplantation on survival, particularly in regions such as China, where the prevalence of CMV IgGpositivity is high. The findings underscore the necessity for devising and executing focused prevention and early management strategies for CMVr and BSI to enhance outcomes for allo-HSCT recipients.